Viewpoints about social networking in the construction of media reality - La Rosa Pinedo, Amaro (2019)
Starting from an appreciation of social networks and daily communication, an approach is made to the knowledge of the impact of social networks on journalistic activity in different realities, based on the most recent scientific evidence at an international level.